(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
English proficiency is a crucial skill for college students, as it is the foundation for effective communication, critical thinking, and academic success. This study aimed to determine the level of English proficiency of incoming first-year college students at Union Christian College (UCC) for the Academic Year 2021-2022. The study specifically investigated their proficiency in four key areas: content words, phrases, and phrase analysis; sentence and sentence analysis; sentence construction; and error analysis. The study employed a descriptive-status research design, utilizing an English proficiency test as the primary data collection instrument. The test was administered to a random sample of 375 incoming first-year students. Frequency counts, weighted means, and pair-wise t-tests analyzed the data. The study revealed that the incoming UCC first-year students exhibited moderate English grammar proficiency overall. While they demonstrated a slightly proficient level in content words, phrases, and phrase analysis, their proficiency was moderate in sentences, sentence analysis, sentence construction, and error analysis. However, the results also indicated constraints in all areas of English grammar assessed. Notably, no significant difference was observed in the English proficiency of incoming first-year students when grouped according to the programs they intended to enroll in. The moderate English grammar proficiency of incoming UCC first-year students highlights the need for ongoing efforts to strengthen their language skills. While they have acquired a basic understanding of English grammar, they require further instruction and practice to achieve the level of proficiency necessary for effective academic engagement and communication. The identified constraints in content words, phrases, and sentences suggest that incoming first-year students may struggle with vocabulary acquisition, idiomatic expressions, and sentence structure. These areas should be emphasized in the EPEP to ensure that students develop a comprehensive understanding of English grammar and usage. The absence of significant differences in English proficiency across academic departments indicates that the identified constraints are not specific to any particular field of study. This suggests that the EPEP should be designed to address the general English language needs of all incoming first-year students, regardless of their chosen majors. The implementation of the EPEP, as the study recommends, will require collaboration between English instructors and potential English clubs. This collaborative approach can provide a well-rounded and supportive learning environment for incoming first-year students, ensuring they receive the necessary guidance and practice to enhance their English language proficiency. By addressing the English proficiency needs of incoming first-year students through the EPEP, UCC can foster a more inclusive and supportive learning environment, enabling students to attain the level of language proficiency necessary for academic success and personal growth.